IMPLEMENTASI REGULASI NASIONAL TERKAIT KESELAMATAN KAPAL PENANGKAP IKAN DI PPN PEKALONGAN - Huda, Muhammad; Boesono, Herry; Setiyanto, Indradi (Journal of Fisheries Resources Utilization Management and Technology, 2012)
The purpose of this study was to obtain an overview of national regulations relating fishing vessel safety, obtain an overview of the implementation of regulations relating fishing vessel safety in the Pekalongan Archipelago Fishing Port and analyze alternative solutions in order to achieve optimization of the application of national regulations relating fishing vessel safety. The method used in this research is descriptive method that is featured a case study with Likert Scale and Analysis Hierarchy Process (AHP)done to be data analyze. The results showed that only the Minister of Communications Decree No.KM 46 Year 1996 regarding Seaworthiness Certification of Fishing Vessels that discussed the safety of fishing vessels. Implementation of regulations related to safety of fishing vessels in the Pekalongan Archipelago Fishing Port within 5 (five) years ranged between 69.31% - 73.08%, it indicates that the rate of application of relevant regulations on the safety of fishing vessels belonging to the Pekalongan Archipelago Fishing Port in both categories based on predefined criteria weighting. Which occupies the first priority action to achieve the optimization of the application of relevant regulations on fishing vessel safety in the Pekalongan Archipelago Fishing Port compliance requirements with the characteristics and conditions of fishing vessels and manning with the priority vector value 0.55. The second priority isthe rules firmness relating safety of fishing vessel from the state with the priority vector value 0.29 and the third priority is the seriousness to the implementation by relevant parties such as the Unit Operator Port (Harbourmaster and Marine Inspector) with the priority vector value 0.16.